Biochemical, immunological, and immunocytochemical evidence for the association of chalcone synthase with endoplasmic reticulum membranes. - Hrazdina, G (1987)
Chalcone synthase [naringenin-chalcone synthase; malonyl-CoA:4-coumaroyl-CoA malonyltransferase (cyclizing), E.C. 2.3.1.74], the key enzyme of flavonoid pathways that was believed to be soluble, has been localized on ribosome-bearing endoplasmic reticulum membranes in the epidermis of buckwheat (Fagopyrum esculentum M.) hypocotyls. Enzyme activity measurement and immunoblots of buckwheat hypocotyl homogenates that were fractionated on linear sucrose density gradients and developed with a specific chalcone synthase antibody and a 20-nm ImmunoGold conjugate showed the presence of chalcone synthase in fractions enriched in endoplasmic reticulum membranes. The presence of chalcone synthase on these membranes was not caused by nonspecific adsorption or entrapment of proteins. Immunocytochemical investigations with both a 5-nm and a 20-nm ImmunoGold conjugate showed that chalcone synthase was associated with the cytoplasmic face of rough (ribosome bearing) endoplasmic reticulum membranes. Plasma membrane, nucleus, plastids, mitochondria, golgi, and the tonoplast were not labeled. These data are consistent with our earlier described model suggesting that the synthesis of phenylpropanoids and flavonoids takes place partially or fully on membrane-associated enzyme complexes.